Continuous Wavelet Transform on the One-sheeted Hyperboloid - Hemmat, A. Askari; Fard, Z. Yazdani (Communications in Mathematics and Applications, 2011)
In this work a constructive theory for the CWT on the one-sheeted hyperboloid, H^1,1, has been developed. The construction is based on the notion of convolution on this manifold. We defined the affine transformations on the H^1,1. These are of two types: motions and dilations. We defined the CWT on H^1,1 through a H^1,1-convolution and derived the corresponding admissibility condition.